2007
DOI: 10.3168/jds.2007-0213
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Listeria Species on Dairy Farms

Abstract: This cross-sectional study determined the prevalence of Listeria spp. in bulk-tank milk on dairy farms in the region of Galicia in northwest Spain. The aim was to identify management practices associated with the presence of Listeria spp. and possible effects on milk hygienic quality. A total of 98 farms was randomly selected on the basis of an expected prevalence of 6.5% for Listeria monocytogenes from 20,107 dairy farms in the region. Bulk-tank milk samples were obtained from 98 farms, fecal samples from lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
57
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 21 publications
7
57
3
2
Order By: Relevance
“…Kabeya et al (2003) reported the Arcobacter spp. prevalence to be 3.6% in Japan, while Aydin et al (2007) reported it to be 6.9% in Turkey, Van Driessche et al (2003) found a prevalence of 39% in Belgium and Vilar et al (2010) found one of 41.7% in Galicia. Kabeya et al (2003) isolated A. butzleri, A. cryaerophilus andA.…”
Section: Discussionmentioning
confidence: 99%
“…Kabeya et al (2003) reported the Arcobacter spp. prevalence to be 3.6% in Japan, while Aydin et al (2007) reported it to be 6.9% in Turkey, Van Driessche et al (2003) found a prevalence of 39% in Belgium and Vilar et al (2010) found one of 41.7% in Galicia. Kabeya et al (2003) isolated A. butzleri, A. cryaerophilus andA.…”
Section: Discussionmentioning
confidence: 99%
“…Sağun et al [17] determined that 2.4% of raw milk samples obtained in Van province located in eastern Turkey, were positive for Listeria spp., where L. monocytogenes was found in 1.2%, L. innocua and L. welshimeri in 0.4% of those samples. Vilar et al [11] detected Listeria spp. in 16.3% of bulk-tank milk samples, where L. monocytogenes was found in 6.1%, L. innocua in 7.1%, L. welshimeri in 1.0% and L. grayi in 2.0% of those samples.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study [10] , L. monocytogenes was isolated from 2.3% of corn samples and 2.6% of hay silage samples, which are similar with our results. Vilar et al [11] [12] isolated L. monocytogenes in 6.66% of silage samples. These results on L. monocytogenes in silage samples are higher than the result obtained from our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations